2011 First International Conference on Instrumentation, Measurement, Computer, Communication and Control 2011
DOI: 10.1109/imccc.2011.61
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Cache Reservation to Maximize Efficiency in Shared Cache Multicores

Abstract: Extracting performance from modern multicore architectures requires that parallel sections be divided into many threads of execution. In order to fully utilize these threads effectively, load balancing has become one of the most important factors that affect the performance of applications on multicores. In this paper, we have shown that the threads that belong to a single, multithreaded application can exhibit a poorly balancing performance. We propose a dynamic cache reservation scheme which can redistribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Cache reservation policy: Qing Wang et al [25] showed that threads that belong to a single, multithreaded application can exhibit a poorly balancing performance. They proposed a dynamic cache reservation scheme which can redistribute the reserved cache space to the critical thread for speeding up during the applications running.…”
Section: Related Workmentioning
confidence: 99%
“…Cache reservation policy: Qing Wang et al [25] showed that threads that belong to a single, multithreaded application can exhibit a poorly balancing performance. They proposed a dynamic cache reservation scheme which can redistribute the reserved cache space to the critical thread for speeding up during the applications running.…”
Section: Related Workmentioning
confidence: 99%